Analysis of Student Tendencies in the Learning Process: Judging from Cheating Behavior - Rachmat Sholahuddin Febry; Ardha Yani; Dini Marliyani; Yola Armita (International Journal of Education and Teaching Zone)
This study discusses the analysis of cheating behavior in the world of education. This type of research uses a qualitative descriptive method. The research subjects were SMP Nurul Khoir Jambi students, with a total population of 94 students and a sample of 34 students. The sampling technique used is random. Then, the data collection techniques used were Google Forms, interviews with two questions, and documentation. This study found that the number of students who often cheated was 15 people, the number of students who sometimes cheated was 10 people, and the number of students who rarely cheated was nine people.